2023
DOI: 10.1111/iej.13990
|View full text |Cite
|
Sign up to set email alerts
|

Intracanal removal and apical extrusion of filling material after retreatment using rotary or reciprocating instruments: A new approach using human cadavers

Thamyres M. Monteiro,
Victor O. Cortes‐Cid,
Marilia F. V. Marceliano‐Alves
et al.

Abstract: AimThis study compared intracanal removal of filling as well as the frequency and volume of extruded material after retreatment with either HyFlex or Reciproc instruments in mandibular teeth from cadavers.MethodologyThe root canals of 14 pairs of contralateral single‐rooted teeth in mandibles of cadavers were instrumented with Reciproc R40 and filled using lateral compaction. The mandibles were scanned in a micro‐computed tomographic (micro‐CT) device before and after retreatment procedures. The contralateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…One reason that may explain why the Wave One Gold instrument and the ProDesign Logic RT have similar ability to remove filling material is that the WOG has a parallelogram cross-section with two cutting edges and asymmetricmotion, which may have reduced the percentage of remaining filling material 16 . The absence of significant differences between the systems for extrusion and intracanal filling material removal may also be associated with the standardized conditions of root canal anatomy, irrigation, and working length 3 , 6 , 8 , 9 , 23 . In these conditions, studies have shown that differences in taper, tip and cross-sectional shape, as well as the operation mode and the number of instruments used, fail to promote significant differences in filling removal 3 , 6 , 8 , 9 , 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One reason that may explain why the Wave One Gold instrument and the ProDesign Logic RT have similar ability to remove filling material is that the WOG has a parallelogram cross-section with two cutting edges and asymmetricmotion, which may have reduced the percentage of remaining filling material 16 . The absence of significant differences between the systems for extrusion and intracanal filling material removal may also be associated with the standardized conditions of root canal anatomy, irrigation, and working length 3 , 6 , 8 , 9 , 23 . In these conditions, studies have shown that differences in taper, tip and cross-sectional shape, as well as the operation mode and the number of instruments used, fail to promote significant differences in filling removal 3 , 6 , 8 , 9 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of significant differences between the systems for extrusion and intracanal filling material removal may also be associated with the standardized conditions of root canal anatomy, irrigation, and working length 3 , 6 , 8 , 9 , 23 . In these conditions, studies have shown that differences in taper, tip and cross-sectional shape, as well as the operation mode and the number of instruments used, fail to promote significant differences in filling removal 3 , 6 , 8 , 9 , 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation